2013
DOI: 10.12659/msm.889480
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of selected Tai Chi exercises in a program of strategic rehabilitation aimed at improving the self-care skills of patients aroused from prolonged coma after severe TBI

Abstract: BackgroundDifficulties in self-care constitute a very common problem for patients recovering from prolonged coma after a severe TBI, and a major factor reducing their quality of life. Effective new rehabilitation programs that would help solve this problem are urgently needed. The purpose of our experiment was to evaluate improvement in this respect in a group of patients aroused from prolonged coma who participated in a goal-oriented rehabilitation program (Rehab-3), enhanced with selected elements of Tai-Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Another RCT compared a weekly 1-hour seated tai chi/qigong session to nonexercise social/leisure activities and reported improvements in mood in the tai chi/qigong group 78. A 2-group comparison study that compared a goal-oriented program enhanced with biweekly tai chi exercises with standard rehabilitation showed improvement in self-care in the tai chi group 82. In a case series of 3 individuals with severe TBI who practiced tai chi over 2 to 4 years postintervention, all participants ambulated without assistance and had a decrease in falls 86…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another RCT compared a weekly 1-hour seated tai chi/qigong session to nonexercise social/leisure activities and reported improvements in mood in the tai chi/qigong group 78. A 2-group comparison study that compared a goal-oriented program enhanced with biweekly tai chi exercises with standard rehabilitation showed improvement in self-care in the tai chi group 82. In a case series of 3 individuals with severe TBI who practiced tai chi over 2 to 4 years postintervention, all participants ambulated without assistance and had a decrease in falls 86…”
Section: Resultsmentioning
confidence: 99%
“…Yoga and tai chi are considered forms of therapeutic exercise, delineated as a skilled service. 77 Of the 10 yoga and tai chi studies that met inclusion criteria, 3 studies were RCTs [78][79][80] ; the others were quasiexperimental studies, [81][82][83] mixed-methods studies, 20,84 or case reports. 85,86 Yoga is an ancient Vedic practice incorporating breath, meditation, and body postures for promoting health.…”
Section: Yoga and Tai Chimentioning
confidence: 99%
“…Notably, aerobic exercises such as tai chi and yoga have been popularly promoted for its potential advantages in healthy and ill-attacked populations [6267]; however, the frequency and burden of exercise after TBI differ from one to another and remain to be further elucidated [68]. …”
Section: The Treatments Targeted On Synapses After Tbimentioning
confidence: 99%
“…Exercises are believed to be effective in improving TBI prognosis; the underlying mechanisms include changing the brain structural integrity by enhancing neurogenesis and angiogenesis with more secretions of growth factors promoting synaptic plasticity [ 59 61 ]. Notably, aerobic exercises such as tai chi and yoga have been popularly promoted for its potential advantages in healthy and ill-attacked populations [ 62 67 ]; however, the frequency and burden of exercise after TBI differ from one to another and remain to be further elucidated [ 68 ].…”
Section: The Treatments Targeted On Synapses After Tbimentioning
confidence: 99%
“…A wide array of pharmaceuticals has been used in experimental and clinical trials to alter the events during the course of TBI, although none have shown much promise [ 8 ]. These include anticholinergics, excitatory amino acid antagonists, endogenous opioid antagonists, catecholamines, serotonin antagonists, modulators of arachidonic acid, antioxidants and free radical scavengers, steroid and lipid peroxidation inhibitors, platelet activating factor antagonists, anion exchange inhibitors, magnesium, gangliosides, calcium channel antagonists, growth factors, antihistamine agents, and stem cells [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%